Factors Influencing the Development of Domestic Tourism in the Erongo Region, Namibia - NGONDO, Ebson; HERMANN, Uwe P.; VENTER, Dewald H. (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024, 2024)
Domestic tourism is viewed as the main driving force of the tourism industry in major economies globally. It has received worldwide recognition as a dynamic part of the industry with enormous potential for growth and is considered a useful tool for socio-economic development. However, in Namibia, as is the case with many developing countries, the sector is academically less explored and economically misrepresented. On that background, the main aim of this study was to understand the key factors influencing the development of domestic tourism in developing economies. The Erongo region of Namibia served as a case study. A structured questionnaire was used to collect usable data from 400 respondents. From this study, it was found that major obstacles to the development of domestic tourism in the study area include affordability and awareness issues, limited infrastructure, and poor government policies. While collaboration amongst stakeholders, robust government policies, and coordinated marketing efforts were identified as key determinants of domestic tourism development, they were also identified as key enabling factors. Consequently, the study recommends differential pricing, augmenting the marketing and promotion of tourism products to domestic tourists, and promoting collaboration among stakeholders.